Predicting potential to benefit from an iron intervention: a randomized controlled trial of double-fortified salt in female Indian tea pluckers. Issue 18 (25th July 2019) - Nevins, Julie EH; Venkatramanan, Sudha; Mehta, Saurabh; Haas, Jere D
Abstract: Objective: The present study examines characteristics of those who benefited from a dietary Fe intervention comprised of salt double-fortified with iodine and Fe (DFS). Design: Data from a randomized controlled trial were analysed to identify predictors of improved Fe status and resolution of Fe deficiency (serum ferritin (sFt) < 12 μg/l) and low body Fe (body Fe (BI) < 0·0 mg/kg) using non-parametric estimations and binomial regression models. Setting: A tea estate in West Bengal, India. Participants: Female tea pluckers, aged 18–55 years. Results: Consuming DFS significantly ( P = 0·01) predicted resolution of Fe deficiency (relative risk (RR) = 2·31) and of low BI (RR = 2·78) compared with consuming iodized salt. Baseline sFt ( β = –0·32 (se 0·03), P < 0·001) and treatment group ( β = 0·13 (se 0·03), P < 0·001) significantly predicted change in sFt. The interaction of baseline BI with treatment group ( β = –0·11 (se 0·06), P = 0·08) predicted the change in BI. DFS did not significantly predict change in Hb and marginally predicted resolution of anaemia (Hb < 120 g/l). Conclusions: Baseline Fe status, as assessed by sFt and BI, and consumption of DFS predict change in Fe status and resolution of Fe deficiency and low BI. Anaemia prevalence and Hb level, although simple and inexpensive to measure, may not be adequate to predict resolution of Fe deficiency in response to an intervention of DFS in similar populations with high prevalence of Fe deficiency and multiple nutritional causes of anaemia. These findings will guide appropriate targeting of future interventions.